2013 IEEE 37th Annual Computer Software and Applications Conference 2013
DOI: 10.1109/compsac.2013.109
|View full text |Cite
|
Sign up to set email alerts
|

Toward Collective Intelligence for Fighting Obesity

Abstract: The emergent prevalence of childhood and adolescent obesity remains one of the most significant health care challenges facing the United States today. On the other hand, breakthroughs in Human-Robot Interaction (HRI) research and the diminishing cost of personal robots and virtual agents along with the ever-increasing use of smart personal devices, suggests that there is room for harnessing the power of ubiquitous intelligent systems that can work in partnership to solve some of our most difficult challenges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Most (8/23, 35%) of the studies focused on promoting a healthy diet and exercise, whereas only 4% (1/23) studies focused on a healthy diet, exercise, and stress management ( Figure 2 and Multimedia Appendix 4 ). In all, 11 out of the 14 (79%) planned or trialed experimental studies [ 26 , 29 - 33 , 35 - 37 , 40 , 43 - 45 ] reported program durations that ranged from 1 hour to 12 months [ 30 - 32 ]. Only 1 study mentioned the intention of comparing algorithms to yield accurate behavioral predictions [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (8/23, 35%) of the studies focused on promoting a healthy diet and exercise, whereas only 4% (1/23) studies focused on a healthy diet, exercise, and stress management ( Figure 2 and Multimedia Appendix 4 ). In all, 11 out of the 14 (79%) planned or trialed experimental studies [ 26 , 29 - 33 , 35 - 37 , 40 , 43 - 45 ] reported program durations that ranged from 1 hour to 12 months [ 30 - 32 ]. Only 1 study mentioned the intention of comparing algorithms to yield accurate behavioral predictions [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all, 11 out of the 14 (79%) planned or trialed experimental studies [ 26 , 29 - 33 , 35 - 37 , 40 , 43 - 45 ] reported program durations that ranged from 1 hour to 12 months [ 30 - 32 ]. Only 1 study mentioned the intention of comparing algorithms to yield accurate behavioral predictions [ 43 ]. In total, 12 studies mentioned the use of a behavior change framework to guide AI chatbot development ( Multimedia Appendix 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another work in which collective intelligence was applied focusing on one of the most illnesses problems of the current society is obesity. Starting from the Human-Robot Interaction research, it is possible to develop a system that employs machine learning algorithms in order to feature a humanoid robot Health Coach that helps to reduce childhood obesity [1]. Other example of this kind of application is chronic disease with elderly patients [18].…”
Section: Use and Application Of Collective Intelligence In Ehealthmentioning
confidence: 99%
“…No one can dispute the fact that it is almost impossible to avoid these deaths, but a high number of lives could be saved if some measures would be adopted. One of the most important factors during these emergencies is the fast information exchange and the use of collaborative techniques 1 Research partially supported by the Spanish project DArDOS (TIN2015-65845-C3-1-R) and the Comunidad de Madrid project SICOMORo-CM (S2013/ICE-3006). The first author is supported by a Universidad Complutense de Madrid -Santander Universidades grant.…”
Section: Introductionmentioning
confidence: 99%
“…The scope of activity monitoring facilitated by the Kinect sensor includes the participant's time spent walking around the house, indoor localization, screen capture and timestamps for medicine consumption, time spent watching TV, interactions with the Humanoid companion, etc. [12].…”
Section: B Multimodal Health Monitoring In Elderly Carementioning
confidence: 99%